Feasibility analysis of ambulatory surgery in pediatric ureteropelvic junction obstruction - Fang, Tong; Lu, Rugang; Chen, Ting (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to investigate the feasibility and safety of laparoscopic pyeloplasty for infants and children in an ambulatory surgery setting.Methods78 children with ureteropelvic junction obstruction (UPJO) admitted to the Department of Urology in Children's Hospital of Nanjing Medical University from 1 January 2023 to 31 July 2024 (the inpatient group) and 74 children with UPJO admitted to the ambulatory ward from 1 January 2023 to 31 July 2024 (the ambulatory group) were retrospectively analyzed. The two groups were compared with respect to operative time, length of hospital stay, hospitalization cost, and postoperative complications.ResultsThere was no statistically significant difference between the two groups in terms of age at surgery, gender, ratio of unilateral UPJO, operative time. The hospitalization cost, length of hospital stay, indwelling urinary catheterization duration, and postoperative double J stent removal time in the ambulatory group were all shorter than those in the inpatient group. There was no significant difference between the two groups in postoperative complications such as reoperation, double J stent replacement, urinary tract infection, fever, vomiting and pain.ConclusionAmbulatory surgery for pediatric UPJO is safe and effective. It reduces length of hospital stay and hospitalization cost, effectively improves bed utilization and turnover rate, and does not cause an increase in complication rates.